Oscillation criteria for high order delay partial differential equations. (1998) - Liu, Xinzhi; Fu, Xilin
Abstract : This paper studies a class of high order delay partial differential equations. Employing high order delay differential inequalities, several oscillation criteria are established for such equations subject to two different boundary conditions. Two examples are also given.